2016
DOI: 10.15406/mojor.2016.05.00195
|View full text |Cite
|
Sign up to set email alerts
|

Osteomyelitis: Identification and Management

Abstract: ObjectiveOsteomyelitis is a severe inflammation within the bone, bone marrow and surrounding soft tissue, that develops secondary to infection with microbial organisms. The objective of this article is to present an over view regarding the identification and management of osteomyelitis. IntroductionOsteomyelitis is acute and chronic inflammatory process based upon the histopathological finding rather than duration of infection. Osteomyelitis occurring primarily in children and adolescents pathogenic micro-orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Reactive new bone in the form of periosteal reaction 35 , 36 is a significant characteristic of bird or reptile osteomyelitis 27 . Other studies have also suggested that in modern mammals bone deformation can also be produced by osteomyelitis 37 . Long-term clinical symptoms include abrupt onset of high fever, local oedema, erythema, non-healing ulcers, sinus tract drainage, sepsis and tissue necrosis 33 , 38 , 39 .…”
Section: Discussionmentioning
confidence: 97%
“…Reactive new bone in the form of periosteal reaction 35 , 36 is a significant characteristic of bird or reptile osteomyelitis 27 . Other studies have also suggested that in modern mammals bone deformation can also be produced by osteomyelitis 37 . Long-term clinical symptoms include abrupt onset of high fever, local oedema, erythema, non-healing ulcers, sinus tract drainage, sepsis and tissue necrosis 33 , 38 , 39 .…”
Section: Discussionmentioning
confidence: 97%